Aspirin reduces lipopolysaccharide-induced pulmonary inflammation in human models of ARDS. Issue 11 (12th January 2017) - Hamid, U; Krasnodembskaya, A; Fitzgerald, M; Shyamsundar, M; Kissenpfennig, A; Scott, C; Lefrancais, E; Looney, M R; Verghis, R; Scott, J; Simpson, A J; McNamee, J; et al.
Abstract : Rationale: Platelets play an active role in the pathogenesis of acute respiratory distress syndrome (ARDS). Animal and observational studies have shown aspirin's antiplatelet and immunomodulatory effects may be beneficial in ARDS. Objective: To test the hypothesis that aspirin reduces inflammation in clinically relevant human models that recapitulate pathophysiological mechanisms implicated in the development of ARDS. Methods: Healthy volunteers were randomised to receive placebo or aspirin 75  or 1200 mg (1:1:1) for seven days prior to lipopolysaccharide (LPS) inhalation, in a double-blind, placebo-controlled, allocation-concealed study. Bronchoalveolar lavage (BAL) was performed 6 hours after inhaling 50 µg of LPS. The primary outcome measure was BAL IL-8. Secondary outcome measures included markers of alveolar inflammation (BAL neutrophils, cytokines, neutrophil proteases), alveolar epithelial cell injury, systemic inflammation (neutrophils and plasma C-reactive protein (CRP)) and platelet activation (thromboxane B2, TXB2). Human lungs, perfused and ventilated ex vivo (EVLP) were randomised to placebo or 24 mg aspirin and injured with LPS. BAL was carried out 4 hours later. Inflammation was assessed by BAL differential cell counts and histological changes. Results: In the healthy volunteer (n=33) model, data for the aspirin groups were combined. Aspirin did not reduce BAL IL-8. However, aspirin reduced pulmonary neutrophilia and tissue damaging neutrophil proteases (Matrix Metalloproteinase (MMP)-8/-9), reduced BAL concentrations of tumour necrosis factor α and reduced systemic and pulmonary TXB2. There was no difference between high-dose and low-dose aspirin. In the EVLP model, aspirin reduced BAL neutrophilia and alveolar injury as measured by histological damage. Conclusions: These are the first prospective human data indicating that aspirin inhibits pulmonary neutrophilic inflammation, at both low and high doses. Further clinical studies are indicated to assess the role of aspirin in the prevention and treatment of ARDS. Trial registration number: NCT01659307 Results.